Efficacy, Safety, and Economics of Innovative Medicines: The Role of Multi-Criteria Decision Analysis and Managed Entry Agreements in Practice and Policy - Fens, Tanja; van Puijenbroek, Eugène P.; Postma, Maarten J. (Frontiers in Medical Technology, 2021)
Through the years, solutions for accelerated access to innovative treatments are implemented in models of regulatory approvals, yet with limited data. Besides efficacy data, providing adequate safety data is key to transferring conditional marketing authorization to final marketing authorization. However, this remains a challenge because of the restricted availability and transferability of such data. Within this study, we set up a challenge to analyze the answers of two questions. First, from regulatory bodies' point of view, we bring the question of whether multi-criteria decision analysis (MCDA) is an adequate tool for further improvement of health technology assessment (HTA) of innovative medicines. Second, we ask if managed entry agreements (MEAs) pose solutions for facilitating the access to innovative medicines and further strengthening the evidence base concerning efficacy and effectiveness, as well as safety. Elaborating on such challenges brought us to conclude that increasing the attention to safety in MCDAs and MEAs will increase the trust of the authorities and improve the access for the manufacturers and the early availability of safe and effective medicines for the patients.